Documenting impossible realities : ethnography, memory, and the as if - Coutin, Susan Bibler; Yngvesson, Barbara, 1941- (Cornell University Press, 2023)
"Explores the limitations of conventional accounts through which belonging is documented, focusing on the experiences of adoptees, deportees, migrants, and other exilic populations, and asks what image of reality appears if the 'real' is engaged through its approximations-the child in an adoptive family; the undocumented forced to as legal citizens; politically disappeared persons known only through their material remains?"--